Germination, seedling growth and anatomical responses of Cucumis sativus cv. MTi2 in different salts and development of germination enhancer - Mohammed, Samar Jasim (2017)
Salinity continues to be one of the most serious environmental problems. One of the strategies in dealing with salinity is producing salt tolerant plants and understanding the effects of salinity on crops. Seed germination is an important stage in the life cycle of plants and understanding of tolerance to salinity during the germination stage is crucial for the establishment and management of plant in saline soils. Many studies had been conducted using the effect of NaCl on seed germination, and although there are other types of salt found in soil, until to date, studies about these salts are still limited. Therefore, this study aimed to compare the effects of NaCl, KCl, MgCl2, MgSO4 and CaCl2 on the germination of MTi2 seed, early seedling growth and anatomical of seedling cotyledon leaves. This study also aimed to develop the liquid enhancer in order to improve the germination of salt stressed MTi2 seed. Five types of salts (NaCl, KCl, MgCl2, MgSO4 and CaCl2) at different concentration (50,100,150, and 200 mM) and deionized water as a control were used with nine replicates for each treatment. A 10 sterilized MTi2 seeds were placed in petri dishes containing 5 ml of deionized water or each salinity solution and placed in a completely randomized design in the growth room at 25 ± 1°C. The number of germinated seeds was recorded daily until day 8. On day 8, the length of the hypocotyl, radicle and the biomass of seedlings was measured and the cotyledon leaves were fixed for anatomical study. Germination percentage, germination rate, seed vigor, relative salt injury rate, salt tolerance was calculated. To develop liquid enhancer, sterilized MTi2 seeds were primed with 300mM NaCl for 72 hours and then treated with Salicylic acid alone (SA) (0.25, 0.5, 0.75, 1mM) and KCl alone (10, 20, 30, 40, 50 mM) and deionized water as a control. Germination parameters were calculated as mentioned before. Following this, the ideal concentration of the SA and KCl was mixed together and was used to study its effectiveness as a germination enhancer on the salt-stressed MTi2 seeds. Data were analyzed using SPSS windows version 22. Data are subjected two way ANOVA at confidence level, p≤0. 05 to determine the significant difference between treatment and followed by Tukey at p≤0. 05 for means comparison. The Study found that the germination response ofMTi2 seed on NaCl, KCl, MgCl2, MgSO4 and CaCl2 is significantly different. MTi2 seeds are able to germinate in KCl and NaCl until the high concentration (200 mM) which is % GP more than 50%. In addition, MTi2 seeds able to germinate in medium and low concentration of CaCl2 (50-100 mM) and MgSO4 (50 mM) but unable to germinate in any concentration of MgCl2. The germination rates and the vigor of seed found higher in KCl and NaCl but lower in CaCl2 and MgSO4. Results also found Relatives Salts Injury Rate of MTi2 germinating seed are very low in KCl and NaCl but higher in CaCl2 and MgSO4. The tolerance level of MTi2 seed on different types of salts can be concluded as follows, KCl > NaCl > CaCl2 > MgSO4 > MgCl2. This study also found that 50 mM KCl increased the germination percentage, germination rate and the vigor of MTi2 seeds. Histological studies revealed that changes of MTi2 cotyledon leaves as a response to NaCl, KCl, MgCl2, MgSO4 and CaCl2 are different. The degree histological changes of MTi2 cotyledon leaves increased as the concentration of salts increased. Another type of saltssignificantly changes the structure and arrangement of the upper epidermis cells, mesophyll tissue and lower epidermis cells, also reduce of intracellular space among the mesophyll cells. Results also found that no anatomical changes of MTi2 cotyledon leaves in any concentration of KCl. Results showed that 0.5-0.75 mM SA and 20-30 mM KCl are the ideal concentration that increased significantly the germination and the early growth of MTi2 seedling compared with control treatment. Moreover, the combination of the ideal concentration of SA (0.5 -0.75 mM) and KCl (20-30 mM) increased the germination and the early growth of MTi2 seedlings more than 1x higher than SA and KCl individually. Salt-stressed MTi2 seeds treated with salicylic acid (SA) and low level of (KCl) can contribute in mitigation of the deleterious effects of salinity stress and improve seed germination percentage, germination rate, seed vigor, seedling length and seedling biomass. It can be concluded that the tolerance level of MTi2 seed on different types of salts can be summarized as follows, KCl > NaCl > CaCl2> MgSO4 > MgCl2. Low concentration of a mixture of KCl and SA can be used as an enhancer to increase germination of salt stressed MTi2 seeds.